Impact of dams on hydrology of river Niger at Lokoja, Nigeria - Jimoh, O.D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
River Niger traverses two humid catchment areas that are separated by a wide expanse of semi-arid environment. Within its lower course, the river has been impounded at two points (Kainji and Jebba) for the sole purpose of generating electricity.  This paper discusses the hydrological regime of the river at Lokoja before and after the first dam (Kainji) was commissioned. It was observed that the annual flow during the post-dam period was lower than that of pre-dam period by 10%. This reduction occurred mainly in September, October and November. The seven-day average low flow increased from 520 m3/s during pre-dam to 800 m3/s during the post-dam periods, while the fifteen-day average low flow increased from 500 to 850 m3/s during the respective period. The flood level (Q10) during the post-dam period was lower than the level during pre-dam. This observation shows that one of the effects of river regulation on low flow at Lokoja is to mitigate the severity of low flows, as well as to reduce maximum daily peak flow. It was also discovered that there were variations in the baseflow (Q90) from the pre-dam to post-dam period.  The increase in Q90 value during the post-dam period could be attributed to changes in land use and agricultural practices.